Optimizing Citrus aurantifolia Juice Marination for Improved Chicken Meat Quality: A Study on pH, Tenderness, Water Retention, and Cooking Loss - Sulaiman, Agus; Wibowo, Ari; Suhardi; Aprylasari, Dede; Haris, M. Ichsan; Wahyuningtyas, Amalina Nur; Nurmasytha, Andi (Faculty of Animal Science Universitas Brawijaya, 2025)
This study investigated the effects of marinating chicken meat with varying concentrations of lime juice (Citrus aurantifolia) on its physical properties, specifically pH, tenderness, water-holding capacity (WHC), and cooking loss. The experimental treatments comprised five lime juice concentrations: P0 (control, 0 mL), P1 (10 mL), P2 (20 mL), P3 (30 mL), and P4 (40 mL). The results revealed significant differences in pH values among treatments: P0 (5.67), P1 (5.25), P2 (5.01), P3 (4.91), and P4 (4.78). Tenderness, expressed as penetration force (mm/g), varied across treatments with the following means: P0 (91.13 mm/g), P1 (80.63 mm/g), P2 (81.00 mm/g), P3 (88.50 mm/g), and P4 (69.00 mm/g). WHC values were recorded as follows: P0 (44.41%), P1 (43.40%), P2 (42.52%), P3 (45.00%), and P4 (43.80%). Cooking loss increased with higher lime juice concentrations: P0 (27.00%), P1 (32.50%), P2 (33.00%), P3 (32.50%), and P4 (34.50%). The findings suggest that lime juice concentration significantly affects both pH and tenderness, with the most favorable results observed at the 20 mL concentration, which yielded a pH of 5.01 and tenderness of 81.00 mm/g. In contrast, no significant effects were observed on WHC and cooking loss across treatments. In conclusion, marination with 20 mL of lime juice enhances the physical quality of chicken meat by improving pH and tenderness, without substantially affecting water retention or cooking loss.